2014
DOI: 10.1002/etc.2431
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acute and chronic effects of wood preservative products in daphnia magna and pseudokirchneriella subcapitata based on the concept of concentration addition

Abstract: The current European legislation requires that combined effects of the active substances and any substance of concern contained in biocidal products are taken into account in environmental risk assessment. The hypothesis whether the consideration of active substances together with all formulation additives that are labeled as presenting an environmental hazard is sufficient for a reliable environmental risk assessment was tested in the present study by investigating 3 wood preservative products. Relevant singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…This observation agrees with other workers, which showed that the loss of triazoles (like propiconazole) through evaporation and leaching is similar every week until stabilization (Woo 2010; Kukowski et al 2017;Kukowski et al 2018Kukowski et al , 2019. Coors et al (2014) also found that PBC, a degradation product of IPBC, leaches much faster than propiconazole. Kjellow et al (2010) found that propiconazole passing through a chromatographic column of sawdust had greater retention than IPBC, which indicates stronger interactions with wood materials.…”
Section: E Wssupporting
confidence: 92%
“…This observation agrees with other workers, which showed that the loss of triazoles (like propiconazole) through evaporation and leaching is similar every week until stabilization (Woo 2010; Kukowski et al 2017;Kukowski et al 2018Kukowski et al , 2019. Coors et al (2014) also found that PBC, a degradation product of IPBC, leaches much faster than propiconazole. Kjellow et al (2010) found that propiconazole passing through a chromatographic column of sawdust had greater retention than IPBC, which indicates stronger interactions with wood materials.…”
Section: E Wssupporting
confidence: 92%
“…Only water-based products were selected for experimental testing to reduce any potential interference of organic solvents with the findings regarding compliance with mixture toxicity expectation. Such interference might result from toxicokinetic (synergistic) interactions as pointed out in [ 4 , 36 ]. Overall, the selected products represented different situations in terms of availability of aquatic toxicity data and the number of additives assigned to the different categories (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…They used three wood preservations and tested effects on algal growth and Daphnia acute immobilization as well as reproduction. However, there remains uncertainty, the prediction based on the concentration-addition concept provided mostly reliable or at least protective estimates for the acute and chronic toxicity of the mixtures [32] .…”
Section: Additivity Of Binary Pesticide Mixturesmentioning
confidence: 99%